IJCM_111A: Awareness of third- and fourth-hand smoking and its implications among medical students - A cross sectional study - Saranya SV; Prabhakar Ram V; Balamurugan S (Wolters Kluwer Medknow Publications, 2024)
Background: The term third hand smoke (THS) may have initially appeared in print in 2006, more widely known in 2009. In that work, the researchers stated that 65.2% of non-smokers and 43.3% of smokers believed THS could harm children and such opinions were associated with the imposition of home smoking bans. Fourth-hand smoke, up to two thirds of cigarette butts terminate in the environment. Objective: To estimate awareness and implication of third- and fourth-hand smoking among Medical students. Methodology: A cross sectional study was conducted among Medical students of a Medical College in South India in the month of April 2023. All Medical students whoever gave consent were included in the study. A pre-designed semi-structured questionnaire was administered in google forms to the study participants and informed consent was obtained from the participants. The Beliefs About Third Hand (BATHS) Scale was used to determine beliefs about THS. The data was initially entered to Microsoft Excel 2010 and analysed using statistical package of social science (SPSS trial version 20.0). Results: Among the 360 participants only 35.6% (128) of participants were aware of third hand smoking and 23.3% (84) of participants were aware about fourth hand smoking. Nearly 222(61.6%) participants had opinion of developing asthma, followed by acute respiratory tract infection and wheeze in children when exposed to third hand smoke. Majority 341(94.7%) and 344 (95.6%) participants out of 360 had opinion that smoking should be banned in home environment and public places respectively. Conclusion: The medical students had less awareness about third hand smoke and its effect on human health, hence measures have to be taken to make medical students aware about it. It can be recommended to incorporate third- and fourth-hand smoking as educational messages in the medical curriculum.